Hubungan Terapi Non Farmakologi terhadap Ganguan Tidur pada Lansia di Desa Sukahurip - Oktaviani, Mayang; Chalid, Desridius (Universitas Malahayati, 2023)
ABSTRACT Elderly is a group that has experienced setbacks in psychological and physiological aspects. Everyone will experience old age, so this stage is a natural and natural stage at the end of the human life phase. The World Health Organization (WHO) categorizes the age limit for the elderly. To determine the effect of non-pharmacological therapy on sleep disturbances in the elderly in Sukahurip village in 2023. This research uses a type of quantitative research with a research design study using a quasi-experiment with a pretest-posttest control group design approach. In this study there was one group of subjects where the group was observed before the intervention was carried out and then observed again after the intervention. The results of this research were that of the total male and female respondents who had the highest score of experiencing sleep disturbances, there were 16 women (53.3%), and the age of the respondents who experienced the highest sleep disturbance in the elderly in Sukahurip village, namely the elderly aged 60 -69 years as many as 21 respondents out of a total of 30 respondents. Where some of the respondents who have jobs include retirees, farmers, employees and housewives who have the highest number of respondents who experience sleep disturbance problems, namely farmers as many as 12 (40%) results of the